O patrimônio documental da ditadura militar brasileira: o papel das assessorias de segurança e informações no contexto das universidades - Jacques, Cesar Augusto Freitas (2014)
National Security Dictatorships deployed in Southern Cone countries set innumerable episodes concerning the violation of human rights. In Brazil, for over twenty-one years military personal and some sectors from civil society were responsible for countless atrocities carried out against citizens, especially regarding the ones who were against the military coup. Inside Brazilian universities, reality was not different because the Academies were known as the most important institutions able to work against repression and as a consequence, they had to be effectively controlled. In the beginning of the 1970 s, Safety and Information Advisors Agencies were created in order to monitor and control all actions of academic communities and also the actions of the ones who positioned themselves against the government. The impact of such measure could be felt by all Brazilian universities, and for more than a decade the Safety and Information Advisors Agencies (ASIs) produced a substantial quantity of documents about the work of its agents as well as registers about the subversives . Taking into consideration the period after the dictatorship and the proposal of a Transitional Justice, considered incomplete in Brazil, it is suggested the reactivation of an institutional body from the Federal University of Santa Maria (UFSM) as an alternative to reach, at least in academic level, the principles of transitional justice whose were still not reached. These principles are: the institutional reform and the rescuing of the institution s memory; for such, it is proposed the granting of free access to the ASI/UFSM files.